Ethical Considerations for Humanizing Refugee Research Trajectories - Patricia Daley (Refuge, 2021)
This paper argues that ethical responsibilities in refugee studies have focused on fieldwork, yet ethics ought to be applied to the research problematic—the aims, questions, and concepts—as potentially implicated in the production of harm. Using an example from Tanzania, I argue that policy has largely shaped the language, categories investigated, and interpretive frames of refugee research, and this article advocates greater attention to historical and contemporary processes underpinning humanitarian principles and practices, and how they might contribute to exclusion and ontological anxieties among refugees in the Global South. By expanding our conceptualization of ethical responsibilities, researchers can better explore the suitability, and the implications for the refugee communities, of the approach that they have adopted and whether they contribute or challenge the and dehumanization of people seeking refuge.